PEMBUATAN BRIKET DAUN DARI LIMBAH PENGOLAHAN MINYAK KAYU PUTIH - Djeni Hendra (Jurnal Penelitian Hasil Hutan, 1992)
The  experimental   study   on  briqueting   from   leaf waste  of  cayeput  oil distillation prepared   by using  the hydraulic press proess  is presented   in  this paper.   The  tapioca  flour   is used  as adhesive  with  five different  consentrations   i.e. 1 per cent,  1.5 percent,   2  percent,    3 percent   and 5 percent.   The  responses  evaluated  are the  moisture  content,  ash  content,  volatile  matter,  density,  crushing  strength  and calorific  value.  The result  shows  that  moisture  content  ranges  from  12,21-  12,86 percent,  ash  content   from   8, 02  -  8,85  percent,    volatile  matter  from  68,  08  -  69, 45 percent,    density   from 0,251 -  0,325 gr/cm3.  crushing sfrength  from  9,60 - 19,82  kg/cm2   and the calorific  value from  4326,46 -  4473.05  cal /gr.